2019
DOI: 10.1111/1756-185x.13727
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory predictions of myocardial inflammation as detected by cardiac magnetic resonance imaging in patients with systemic sclerosis: A pilot study

Abstract: Background: Cardiac magnetic resonance imaging (cardiac MRI) has high sensitivity and specificity for differentiating cardiac fibrosis from inflammation. There is no data on the clinical and laboratory association or prediction of myocardial inflammation in systemic sclerosis-a major organ involvement in systemic sclerosis (SSc). Objectives:Our aim was to ascertain the clinical and laboratory associations with myocardial inflammation in SSc patients as detected by cardiac MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
0
0
Order By: Relevance
“…Our results also indicated that an increased CK‐MB level was an independent risk factor for death. CK‐MB is a major indicator of myocardial damage, and our results support the interpretation that cardiac involvement of SSc patients is responsible for this increased risk of death 40 . In addition, some patients with SSc have myositis, which can also increase the level of CK and CK‐MB.…”
Section: Discussionsupporting
confidence: 86%
“…Our results also indicated that an increased CK‐MB level was an independent risk factor for death. CK‐MB is a major indicator of myocardial damage, and our results support the interpretation that cardiac involvement of SSc patients is responsible for this increased risk of death 40 . In addition, some patients with SSc have myositis, which can also increase the level of CK and CK‐MB.…”
Section: Discussionsupporting
confidence: 86%
“…reported the myocardial inflammation according to the Lake Louise Criteria, [ 18 ] from cardiac magnetic resonance imaging during the early onset of SSc (within 4 years of onset), specifically in patients with the dcSSc subset. [ 8 ] The authors also found a combination of myocardial scar and myocardial inflammation from cardiac MRI in the same patients. [ 8 ] Regarding the longer median duration of disease in our SSc patients compared to those in the study by Tipparot et al ., our findings may represent the late complication of myocardial involvement in SSc, which should be associated with myocardial fibrosis rather than myocardial inflammation.…”
Section: Discussionmentioning
confidence: 93%
“…[ 8 ] The authors also found a combination of myocardial scar and myocardial inflammation from cardiac MRI in the same patients. [ 8 ] Regarding the longer median duration of disease in our SSc patients compared to those in the study by Tipparot et al ., our findings may represent the late complication of myocardial involvement in SSc, which should be associated with myocardial fibrosis rather than myocardial inflammation. Although we could not determine whether our patients had myocardial inflammation and/or fibrosis during follow-up or the duration of myocardial fibrosis because cardiac MRI was not a routine investigation in our cohort owing to budget constraints, the findings can provide insight into the natural course of myocardial involvement in SSc.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Background: Systemic sclerosis (SSc) is an autoimmune connective tissue disease characterized by progressive cutaneous and visceral fibrosis, and disseminated vasculopathy [1]. Due to clinical features, SSc patients may present low muscle mass, which impacts negatively on their daily activities and physical function [2,3]. There are several methods to assess muscle mass such as magnetic resonance imaging (MRI), computed tomography (CT) and dual-energy radiological absorptiometry (DXA).…”
Section: Discussionmentioning
confidence: 99%